P01.165 A prospective study investigating the Impact Of MultidiscipliNarY tumor Board in brain tumor management: the OMNYBuS Project. (19th September 2018) - Chiesa, S; Sabatino, G; Gaudino, S; La Rocca, G; Mazzarella, C; Beghella Bartoli, F; Colosimo, C; Valentini, V; Olivi, A; Balducci, M
Abstract: Background: Multidisciplinary clinics have become the standard practice for cancer care worldwide. The aim of the OMNYBuS project is to investigate the impact of tumor board in brain tumor management in order to obtain the best personalized treatment plan. Material and Methods: In the first phase of the study, we collected data retrospectively obtained from the first year experience of multidisciplinary tumor board. Neurosurgeons, radiation oncologist, radiologist, anatomopathologists and residents were involved in the multidisciplinary discussion. The analysis was conducted in order to arrange a strategy of the prospective phase. The primary endpoint was the management change rate in terms of exchange, addition, or subtraction of treatment modality. The secondary endpoints were the delay considering treatment starting time, extra diagnostic work-up and time needed for academic discussion Results: Between March 2017 and March 2018, 148 consecutive cases were presented and discussed in terms of diagnostic imaging results and interpretation, medical, surgical, and/or radiation treatment planning, and pathology results and interpretation. The discussed cases were: 33, 3% high grade gliomas, 10, 8% anaplastic astrocytomas, 6, 5% oligodendrogliomas, 2, 2% low grade gliomas, 14% meningiomas, 14% single metastases, 8, 6% multiple metastases, 5, 4% other type of lesion. The terapheutic plan change rate was 9.2%, mostly for high grade gliomas. No delay was observed in treatment starting time. A reduction of diagnostic work-up accounted for 65, 7%. The median time for case discussion was 10 minutes with a median tumor team members presence of 22 clinicians. Conclusion: This data emphasizes the fact that in a relevant number of cases the initial treatment strategy could be modified after a multidisciplinary discussion. Almost all respondents indicated that these meetings were "very beneficial" to their own practice and this retrospective phase allows us to elaborate a data collection strategy to prospective analyze the adherence to guidelines, the reduction of diagnostic work-up and the patients related outcomes. We are using the new schedule for data collection in our multidisciplinary clinical practice